2023
DOI: 10.3390/horticulturae9020142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Global Warming on the Yields of Strawberry in Queensland: A Mini-Review

Abstract: Light, temperature and rainfall affect the growth and yield of strawberry plants (Fragaria × ananassa Duch.). The objective of this review was to determine the impact of global warming on the yields of strawberry in a temperate (summer crop) and subtropical environment (winter crop) in southern Queensland, Australia. Information was collected on the changes in temperature over five decades in two locations in this area. The relationship between relative yield and temperature from published data was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Research in Japan suggests that there is close agreement between CO 2 assimilation in leaves and the canopy only under high light and high CO 2 (Le et al, 2021). A recent analysis indicated that yield decreases by 60 g per plant for each 1°C increase in temperature (Menzel, 2023). However, this study did not take into account changes in carbon production under climate change.…”
Section: Effect Of Climate Change On Photosynthesis Leaf Area Expansi...mentioning
confidence: 79%
“…Research in Japan suggests that there is close agreement between CO 2 assimilation in leaves and the canopy only under high light and high CO 2 (Le et al, 2021). A recent analysis indicated that yield decreases by 60 g per plant for each 1°C increase in temperature (Menzel, 2023). However, this study did not take into account changes in carbon production under climate change.…”
Section: Effect Of Climate Change On Photosynthesis Leaf Area Expansi...mentioning
confidence: 79%
“…Hence, the response of strawberries to increased temperature may therefore be different from other crops. Strawberry productivity decreases when elevated CO 2 is combined with elevated temperature [26]. Himali et al reported that an increase in the intercellular to atmospheric CO 2 ratio (Ci/Ca) at high temperatures may reduce photosynthesis, and thus reduce strawberry yield.…”
Section: Introductionmentioning
confidence: 99%
“…This expansion increases the need to find alternative energy resources that are completely free from all negative impacts on the Earth, such as greenhouse gas (GHG) emissions. The evaluation of carbonaceous wastes such as biomass is considered a reliable clean energy source [2]. Industrial wastes, agricultural wastes, food wastes, and wastewater represent different types of biomasses.…”
Section: Introductionmentioning
confidence: 99%